2003
DOI: 10.1103/physrevlett.90.075005
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Plasma Startup by Coaxial Helicity Injection

Abstract: The first successful results on the transfer of a coaxial helicity injection (CHI) produced discharge to inductive operation are reported. CHI-assisted plasma startup is more robust than inductive only operation. After hand off for inductive operation, the initial 90 kA of CHI-produced current drops to 40 kA, then ramps up to 170 kA, using only 30 mV s, more than 30% higher than that produced by induction alone. These significant performance enhancing results were obtained on the HIT-II spherical torus experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…On HIT-II, a new type of CHI termed "transient CHI" was developed 146,147 where, with the injector flux footprints sufficiently close together, the injector current is rapidly reduced to zero. This causes the oppositely directed field lines in the injector region to reconnect causing closed flux surfaces.…”
mentioning
confidence: 99%
“…On HIT-II, a new type of CHI termed "transient CHI" was developed 146,147 where, with the injector flux footprints sufficiently close together, the injector current is rapidly reduced to zero. This causes the oppositely directed field lines in the injector region to reconnect causing closed flux surfaces.…”
mentioning
confidence: 99%
“…In addition, once the discharge initiated, as a result of the significant external inductance required to operate the power supply the injector current could not be rapidly reduced, as required for transient CHI. Experiments on the HIT-II concept exploration device showed that a capacitor based power supply would be more suitable for transient CHI startup [12]. As a result a suitable power supply was designed to meet the requirements for transient CHI operation in NSTX.…”
Section: Hardware Upgrades That Enabled Implementation Of Transient Cmentioning
confidence: 99%
“…However, for the purpose of initial plasma startup it was found in the HIT-II ST that a new mode of CHI operation in an ST, referred to as transient CHI [12], which involves only axisymmetric magnetic reconnection works very well and produces useful closed flux equilibrium. In transient CHI, the initial poloidal field configuration is chosen such that the plasma carrying the injected current rapidly expands into the chamber.…”
Section: Introductionmentioning
confidence: 99%
“…It has allowed HIT-II consistently to produce higher current discharges than was possible by induction alone. It is largely insensitive to field errors and changing wall conditions (11) .…”
Section: Transient Chimentioning
confidence: 99%
“…This mode of CHI operation can be referred to as steady state CHI, during which the CHI injector circuit is continuously driven for some time (t pulse > t L/R ). A very significant development during the past two years has been the demonstration of a new mode of CHI operation, referred to as transient C H I (11) . This mode involves an axisymmetric reconnection and has been highly successful on the HIT-II experiment.…”
Section: Introductionmentioning
confidence: 99%